Analisis Pendistribusian Laba Dalam Akuntansi Syariah Untuk Mencapai Prinsip Keadilan - Salsabila Dwi Ananda; Nurlaila Nurlaila (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The purpose of this research is to determine the description of profit sharing in sharia accounting to achieve the principles of justice. This research uses a qualitative descriptive approach with a post-positivist paradigm. The informants in this research used data collection techniques using interviews, observation and documentation. Research shows that the profits generated by companies are not just the result of the work of a group of people. However, many stakeholders are involved, including fund owners, employees and the environment. With an impartial perspective, profits can benefit all parties involved, not just a handful of executives.